Samtidskunsthistorie? Noter om samtidskunst og kunsthistoriefaget i dag: Samtidskunsthistorie? Noter om samtidskunst og kunsthistoriefaget i dag - Vest Hansen, Malene (Periskop – Forum for kunsthistorisk debat, 2022)
ABSTRACT “Contemporary art history? Notes on contemporary art and art history today” discusses the significant role played by contemporary art in art history as an academic discipline today, based on the understanding of both contemporary art and art history as informing the radical postmodern changes in conceptions of art, history, canon, gender, and colonialism. Taking as a starting point the case of art history at the University of Copenhagen, Denmark since the 1990s and the author’s experiences through more than three decades working as an art historian and art critic, the article draws on specific case studies of contemporary art projects and the art history journal Periskop to argue that contemporary art has played a key role in changing the traditional academic art historical discipline into a “new art history”. Moreover, the essay discusses why an (art) historical perspective is also vital for the contemporary understanding of and working critically with contemporary art by addressing discussions of key ideas formulated by international art historians, including Terry Smith’s “contemporaneity”, Claire Bishop’s “dialectical contemporaneity”, and David Joselit’s “strategies of re-authorization”.